Dietary intake of glucoraphanin during pregnancy and lactation prevents the behavioral abnormalities in the offspring after maternal immune activation - Yuko Fujita; Atsuhiro Fujita; Tamaki Ishima; Ayumi Hirai; Shigenori Suzuki; Hiroyuki Suganuma; Kenji Hashimoto (Neuropsychopharmacology Reports, 2020)
Abstract Aim Epidemiological data suggest that maternal immune activation (MIA) plays a role in the etiology of neuropsychiatric disorders including autism spectrum disorder (ASD) and schizophrenia. However, there is no prophylactic nutrition that can prevent the onset of neurodevelopmental disorders in offspring after MIA. The aim of this study was undertaken to examine whether dietary intake of glucoraphanin (GF: the precursor of a natural anti‐inflammatory compound sulforaphane) can prevent the onset of behavioral abnormalities in offspring after MIA. Methods One percent of GF food pellet or normal food pellet was given into female mice during pregnancy and lactation (from E5 to P21). Saline (5 mL/kg/d) or poly(I:C) (5 mg/kg/d) was injected into pregnant mice from E12 to E17. Behavioral tests and immunohistochemistry of parvalbumin (PV) were performed in male offspring. Results Dietary intake of GF during pregnancy and lactation prevented cognitive deficits and social interaction deficits in the juvenile offspring after MIA. Furthermore, dietary intake of GF during pregnancy and lactation prevented cognitive deficits in the adult offspring after MIA. Moreover, dietary intake of GF prevented the reduction of PV immunoreactivity in the medial prefrontal cortex of adult offspring after MIA. Conclusion These data suggest that dietary intake of GF during pregnancy and lactation could prevent behavioral abnormalities in offspring after MIA.